Motivation factor that influence worker’s productivity in oil palm plantation: a case study in Mados’s Mersing estate / Muhammad Safuan Sallehudin - Sallehudin, Muhammad Safuan (Faculty of Plantation and Agrotechnology, 2018)
High level of workers’ performance and productivity is becoming one of important factors for any organization success. Due to this reason several factors needed to be studied and investigated. Aim of this study was to identify motivation factors that influence worker’s productivity (Act as dependent variable) of a plantation workers based on the four factors which are Organizational Behavior, Training, Environment of Workplace, and Salary and Reward. Methods for this research is survey using questionnaires. This research located at Mersing, Johor. Total respondent for this research are 87 respondents and were managed to be usable and valid for the further analysis of data. All the data recorded and analysed using Statistical Package for Social Science (SPSS) consist of correlation coefficient and multiple regression. Result shows that salary and reward give the higher positive impact on the employee performances at Mersing Estate, salary and reward can help to improve their economic status as the basic payment rate as general workers is low so workers will make the salary and reward as a motivation to improve their performance thus productivity increase. Followed by training, all workers need training to improve their performance and enhance their skills and automatically their level of performances and productivity will be increase. Furthermore, environment of workplace must be in good condition as to provide best accommodation and facility that can influence the motivation of the worker in Mersing Estate thus the performances and productivity of the workers increase. Lastly, the organization behavior, usually general workers have a union to protect them. Within the union, the management will care about the welfare and build the better organization behavior toward the workers. As for the recommendation,Mersing Estate management need to give their workers more opportunity to make extra work or overtime for the certain operation, in example manuring to increase their basic salary. Lastly to become more efficient and effective Mersing Estate need improvise their technology and provide good accommodation and training system toward the worker to enhance good performances and productivity.